Jaminan Hak Atas Tanah Sertifikat Yang Diperoleh Dari Pewarisan Dalam Pembebanan Hak Tanggungan - Lina Maulidiana; Rendy Renaldy (Universitas Sang Bumi Ruwa Jurai, 2019)
The role of financial institutions or banks is very important in meeting the needs of funds for the community, one of which is by providing credit. The practice of granting credit from the Bank is known as a method called Mortgage Rights as a credit guarantee institution to the community in order to develop their business, in which the certificate of ownership of land is given to a notary to check the authenticity of the certificate before being encumbered. Certificate checks are carried out at the The Ministry of Agrarian Affairs and Spatial Planning/National Land Agency office in accordance with the location of the certificate land. The certificate obtained from the inheritance usually results in conflict if one of his heirs does not approve of the existence of a debt owed by one who collateralizes the certificate.This study uses the socio legal method which is to examine the implementation or implementation of positive legal provisions (legislation) and contractual factual in every particular legal event that occurs in the community in order to achieve the goals that have been determined.The results of the study can be concluded that the imposition of Underwriting Rights on certificates obtained from inheritance if the beneficiary has not been divided or has not yet returned the name can be done if all the heirs come to approve and know through the signature as proof of approval, if there is one heir who does not want to sign or do not agree, then the imposition of Mortgage Rights cannot be imposed. There are 2 (two) legal protections for creditors over disputes over ownership of land rights that are encumbered with Mortgage Rights. Ie, preventive legal protection (prevention) and repressive legal protection (coercion). If the creditor has tried through preventive measures and ultimately the credit is problematic, then the creditor will use repressive measures. Repressive measures that will be carried out are efforts to save credit through non-litigation.